Ethical practice in professional nursing care - Cervera Vallejos, Mirtha Flor (2023)
It is known that ethics has high aspirations; Acting ethically frees us from doubt, encourages prudence in decision-making and clarifies the routes to follow in a world full of opportunities, virtues and vices. I invite you to reflect on an inescapable truth: EPs aspire to self-improvement, to constant growth in daily life. Nursing can guide their ethical actions towards the benefit of others, applying ethical and deontological principles in their professional practice. This guarantees humanized and responsible care, respecting life and human rights